2017
DOI: 10.1016/j.rmed.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations and duration of smoking abstinence are associated with the annual loss of FEV1 in individuals with PiZZ alpha-1-antitrypsin deficiency

Abstract: Annual decline in FEV is related to the exacerbation rate, occupational dust exposure and the duration of smoking abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
4
0
1
Order By: Relevance
“…We found that frequent exacerbations were associated with accelerated loss of FEV 1 . Our findings are in accordance with previous studies of usual COPD and in AATD patients 9,10,12,13,20…”
Section: Discussionsupporting
confidence: 94%
“…We found that frequent exacerbations were associated with accelerated loss of FEV 1 . Our findings are in accordance with previous studies of usual COPD and in AATD patients 9,10,12,13,20…”
Section: Discussionsupporting
confidence: 94%
“…Our review suggests that patients with AATD who have frequent exacerbations (⩾3 per year) or chronic sputum expectoration have a poorer QoL than patients without [74], and that SGRQ scores may be significantly correlated with both exacerbations and dyspnoea [76]. Exacerbations are often associated with long-term sequelae including significant, permanent loss of lung function [26,129,130]. However, exacerbations are random events that are driven by infections and outcomes can vary substantially.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study also support the findings of previous limited analyses of ZZ-AATD patients. The national German registry analysis with patients who had not received augmentation therapy (n=15) and patients who did receive therapy (n=85) over a mean follow-up of 4.89 years [ 22 ] showed no difference in FEV 1 decline between groups. Neither did the analysis of the Spanish national database of patients who did not receive augmentation therapy (n=45) and patients who did receive augmentation therapy (n=77) over an average of >8 years [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the registry does not include data about the use and timing of long-acting bronchodilators on the day of the spirometry. Fourth, several other factors are known to influence FEV 1 decline in AATD: baseline FEV 1 , smoking history, age, body mass index (BMI) and exacerbation rate [ 22 , 26 ]. In our database, no exacerbation rate or respiratory symptoms are registered, apart from the St. George's Respiratory Questionnaire score at baseline.…”
Section: Discussionmentioning
confidence: 99%